Studi Kritis Terhadap Pandangan Muhammad Al-Ghazali Tentang Hadis Âhâd dalam Kitab As-Sunnah Al-Nabawiyyah Baina Ahl Al-Fiqh Wa Ahl al-Hadits - Ardiansyah Ardiansyah; Heri Firmansyah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
A Critical Study of Muhammad Al-Ghazali's View of the Âhâd Hadith in the Book of As-Sunnah Al-Nabawiyyah Baina Ahl Al-Fiqh Wa Ahl al-HaditsOne of the leading contemporary muhaddist scholars who came from Egypt is Sheikh Muhammad Al-Ghazali. Among his monumental works in the study of hadith is a book of hadith criticism entitled